Attitudes towards vocational teaching and its relationship with vocational interests and awareness for 10 grade students in Sultanate of Oman = الاتجاهـات نحـو التعليـم المهنـي وعلاقتـه بالوعـي المهني لـدى طلبـة الصـف العاشـر فـي سلطنـة عمـان - Ali Zayid, Al-Shibli Rashid; Abd. Hamid, Siti Rafiah; Al Bakor, Fahmi Mostafa (International Organization Center of Academic Research (OCERINT), 2020)
This quantitative study discusses the attitudes of tenth grade students in North Al Batinah governorate towards vocational education, where the problem highlights that the numbers of students enrolled in vocational training are very few, compared to the numbers of students enrolled in general and basic education, the specializations in the professional branches are very few, which do not meet the needs and requirements of the labor market. This is in addition to the lack of awareness among students and their parents of vocational education. Therefore, the aim of the study is to reveal the level of students' attitudes towards vocational education. Knowing their attitudes towards vocational education and its relationship to professional awareness. And reveal the responses of male and female students according to the scale of attitudes towards vocational education. The study adopted the descriptive, relational approach. A random sample of 393 students was chosen from the study population, and 387 students from all six states. Three measures were used: the measure of the trend towards vocational education (30) statements, the scale of occupational awareness (30) statements, the scale of occupational interests (24) statements. The results indicated that students ’attitudes toward vocational education were positive to a low degree, a statistically significant correlation at level (0.01) between the trend towards vocational education, and vocational awareness among the study sample individuals in the vocational awareness scale, and a statistically significant correlation at level (0.01) between the trend towards vocational education , And professional interests of the study sample, and finally, there are no differences between male and female students in the direction towards vocational education. ****************************************************************************** تناقش هذه الدراسة الكمية اتجاهات طلبة الصف العاشر في محافظة شمال الباطنة نحو التعليم المهني، حيث تبرز المشكلة أن أعداد الطلبة الملتحقين بالتدريب المهني قليلة جدا، مقارنة بأعداد الطلبة الملتحقين بالتعليم العام والأساسي. وأن التخصصات فـي الفروع المهنية قليلة جدا، لا تلبي احتياجات ومتطلبات سوق العمل. هذا إلى جانب عدم وعـي الطلبة وأولياء أمورهم بالتعليم المهني. لذا تهدف الدراسة: الكشف عـن مستوى اتجاهات الطلبة نحو التعليم المهني. التعرف إلى اتجاهاتهم نحو التعليم المهني وعلاقته بالوعي المهني. والكشف عن استجابات الطلاب والطالبات وفق مقياس الاتجاهات نحو التعليم المهني. اعتمدت الدراسة المنهج الوصفي الارتباطي، تم اختيار عينة عشوائية من مجتمع الدراسة قدرها (393) طالبا، و(387) طالبة من جميع الولايات الست. استخدمت ثلاث مقاييس هي: مقياس الاتجاه نحو التعليم المهني (30) عبارة، مقياس الوعـــــــــــــــي المهنــــــــــــــــي (30) عبارة، مقياس الاهتمامات المهنية (24). دللت النتائج: أن اتجاهات الطلبة نحو التعليم المهني كانت إيجابية بدرجة متدنية، وجود ارتباط دال إحصائيا عند مستوى 0.01 بين الاتجاه نحو التعليم المهني، والوعي المهني لدى أفراد عينة الدراسة في مقياس الوعي المهني، وجود ارتباط دال إحصائيا عند مستوى 0.01 بين الاتجاه نحو التعليم المهني، والاهتمامات المهنية لدى أفراد عينة الدراسة، وأخيراً عدم وجود فروق بين الطلاب والطالبات في الاتجاه نحو التعليم المهني.